Пылающие сердца: роман / Джоанна Линдсей - Линдсей Джоанна (Шарм, 2001)
Экземпляры: АБ (20180924) / Инвентарный номер: 42418 / Цена: 38.40 / Сис.шифр: 84(7Сое) / Авт.знак: Л 59 / ГРНТИ: 17.82.31 / ББК: 84(7Сое)